Myelin Plasticity and Repair: Neuro-Glial Choir Sets the Tuning - Ronzano, Remi; Thetiot, Melina; Lubetzki, Catherine; Desmazieres, Anne (Frontiers in Cellular Neuroscience, 2020)
Plasticity of the central nervous system (CNS) in response to neuronal activity has been suggested as early as 1894 by Cajal. CNS plasticity has first been studied with a focus on neuronal structures. However, in the last decade, myelin plasticity has been unraveled as an adaptive mechanism of importance, in addition to the previously described processes of myelin repair. Indeed, it is now clear that myelin remodeling occurs along life and adapts to the activity of neuronal networks. Until now, it has been considered as a two-part dialog between the neuron and the oligodendroglial lineage. However, other glial cell types might be at play in myelin plasticity. In the present review, we first summarize the key structural parameters for myelination, we then describe how neuronal activity modulates myelination and finally discuss how other glial cells could participate in myelinic adaptivity.